2023
DOI: 10.3390/antiox12051042
|View full text |Cite
|
Sign up to set email alerts
|

GlyNAC (Glycine and N-Acetylcysteine) Supplementation in Old Mice Improves Brain Glutathione Deficiency, Oxidative Stress, Glucose Uptake, Mitochondrial Dysfunction, Genomic Damage, Inflammation and Neurotrophic Factors to Reverse Age-Associated Cognitive Decline: Implications for Improving Brain Health in Aging

Abstract: Cognitive decline frequently occurs with increasing age, but mechanisms contributing to age-associated cognitive decline (ACD) are not well understood and solutions are lacking. Understanding and reversing mechanisms contributing to ACD are important because increased age is identified as the single most important risk factor for dementia. We reported earlier that ACD in older humans is associated with glutathione (GSH) deficiency, oxidative stress (OxS), mitochondrial dysfunction, glucose dysmetabolism and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…Cys and Cys-Gly play an important role in GSH-directed antioxidant activity and sulfur exchange between amino acids, such as the conversion from Cys to taurine. A change in Cys/Cys-Gly level may alter the activity of the antioxidant system (Kumar et al, 2022) and the metabolism of some biologically active substances in the body (Kumar et al, 2023). Combined with the changes in the serum biochemical indicators, our study suggests that supplementation of VC may directly enhance the reducing property of GSH rather than increasing its level.…”
Section: Discussionmentioning
confidence: 66%
“…Cys and Cys-Gly play an important role in GSH-directed antioxidant activity and sulfur exchange between amino acids, such as the conversion from Cys to taurine. A change in Cys/Cys-Gly level may alter the activity of the antioxidant system (Kumar et al, 2022) and the metabolism of some biologically active substances in the body (Kumar et al, 2023). Combined with the changes in the serum biochemical indicators, our study suggests that supplementation of VC may directly enhance the reducing property of GSH rather than increasing its level.…”
Section: Discussionmentioning
confidence: 66%
“…When NAC was given alone, it accelerated senescence and shortened the lifespan of the nematode worm Caenorhabditis elegans [ 27 ]. Recent studies have found that the GlyNAC complex can correct GSH deficiency, counteract oxidative stress, correct type II diabetes, reduce insulin resistance, enhance muscle strength, and improve cognitive function in older adults, suggesting that it has anti-aging effects [ 28 30 ]. However, no study to date has assessed the effects of GlyNAC in SCI.…”
Section: Discussionmentioning
confidence: 99%
“…A study over 8 weeks showed that elderly mice supplemented with Gly and NAC exhibited significant improvements in cognitive function and brain health, reversing declines seen in a control group of elderly mice. 64 In a placebo-controlled trial, elderly participants receiving Gly and NAC for 16 weeks showed improvements in glutathione deficiency, oxidative stress, and mitochondrial dysfunction. 65 Moreover, Gly supplementation can extend the lifespan of mice.…”
Section: Other Antioxidants and Supplementsmentioning
confidence: 99%